2022
DOI: 10.3390/ani12192709
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens: A Review of Their Impacts on Reproductive Physiology and Other Effects upon Grazing Livestock

Abstract: Legume crops and pastures have a high economic value in Australia. However, legume species commonly used for grazing enterprises have been identified to produce high concentrations of phytoestrogens. These compounds are heterocyclic phenolic, and are similar in structure to the mammalian estrogen, 17β-estradiol. The biological activity of the various phytoestrogen types; isoflavones, lignans and coumestans, are species-specific, although at concentrations of 25 mg/kg of dry matter each of the phytoestrogen typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
3
14
0
Order By: Relevance
“…Compared with the corn silage‐fed buffalo cows, the ovaries of Berseem clover‐fed buffalo cows are characterised by improved follicular growth and higher numbers and diameters of large follicles at the day of oestrus with no change in the numbers of CLs but lower diameters of CLs. These findings are partially in accordance with those found in ewes grazing Subterranean clover (subclover) isoflavones (genistein, formononetin and biochanin A) whose ovaries had greater numbers of follicles, with many being deficient in antrum formation leading to early follicular atresia (Wyse et al, 2022). In mammals, the ovarian cells express two types of ERs (Erα and Erβ), having several physiological roles in the development and function of the ovary (Paterni et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Compared with the corn silage‐fed buffalo cows, the ovaries of Berseem clover‐fed buffalo cows are characterised by improved follicular growth and higher numbers and diameters of large follicles at the day of oestrus with no change in the numbers of CLs but lower diameters of CLs. These findings are partially in accordance with those found in ewes grazing Subterranean clover (subclover) isoflavones (genistein, formononetin and biochanin A) whose ovaries had greater numbers of follicles, with many being deficient in antrum formation leading to early follicular atresia (Wyse et al, 2022). In mammals, the ovarian cells express two types of ERs (Erα and Erβ), having several physiological roles in the development and function of the ovary (Paterni et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Among different subclasses of flavonoids, isoflavones are ranked the most biologically active oestrogenic compounds(Křížová et al, 2019), confirming the higher oestrogenic activity of Berseem clover than corn silage.Buffalo cows fed either Berseem clover or corn silage possessed different ovarian activity during the premating period, follicular and luteal phases of the synchronized oestrus and early pregnancy.Compared with the corn silage-fed buffalo cows, the ovaries of Berseem clover-fed buffalo cows are characterised by improved follicular growth and higher numbers and diameters of large follicles at the day of oestrus with no change in the numbers of CLs but lower diameters of CLs. These findings are partially in accordance with those found in ewes grazing Subterranean clover (subclover) isoflavones (genistein, formononetin and biochanin A) whose ovaries had greater numbers of follicles, with many being deficient in antrum formation leading to early follicular atresia(Wyse et al, 2022). In mammals, the ovarian cells express two types of ERs (Erα and Erβ), having several physiological roles in the development and function of T A B L E 3 Ovarian activity of buffalo cows fed roughage with different oestrogenic activity.…”
supporting
confidence: 87%
“…This is evident from the earliest descriptions of reduced fertility in sheep. Although all sheep graze on plants that contain numerous botanical estrogens, reduced fertility occurred in those that grazed exclusively on a type of red clover that contains a high proportion of botanical estrogens with potencies above the HRPT of Borgert et al (2018), such as Biochanin A, formononetic, coumestrol and genistein (Wyse et al 2022). Thus, to be credible, hazard identification of EDCs should consider the potency of the substance at the molecular target and physiologically achievable concentrations of the substances (Autrup et al 2015(Autrup et al , 2020, and as demonstrated by the current analysis, whether physiologically achievable concentrations can overcome baseline occupancy of the molecular target by the endogenous metabolome.…”
Section: Resultsmentioning
confidence: 99%
“…All these protein-rich plant materials, especially soybean, also act as potent sources of non-steroidal secondary metabolites known as phytoestrogens [10]. Phytoestrogens are polyphenolic plant-produced natural compounds that are classified based on their structures: phenolic acids, isoflavonoids, flavonoids, stilbenoids, chalconoids, coumestans and lignans [10,11] (Figure 1). Phytoestrogens are synthesized in plants via various enzymatic pathways, mainly as a response to environmental stress or disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…They also display an ability to bind with estrogen receptors (ERs) and act as endocrine disruptors by affecting the affinity and number of ERs [12]. The literature abounds with studies that focus on the effects of phytoestrogens, especially genistein, which is contained in soybean meal, and on the reproductive functions of various animals, including fishes [5,11,13]. The effects of genistein have been studied in channel catfish (Ictalurus punctatu) [14], Cyprinus carpio [3], goldfish (Carassius auratus) [15] and Pimephales promelas [16].…”
Section: Introductionmentioning
confidence: 99%